2020
DOI: 10.3389/fenvs.2020.00038
|View full text |Cite
|
Sign up to set email alerts
|

Soil Phosphorus Fractionation as Affected by Paper Mill Biosolids Applied to Soils of Contrasting Properties

Abstract: Industrial by-products such as paper mill biosolids (PBs) have been used as fertilizers and amendments in agriculture for many decades. However, their content of plant essential nutrients including phosphorus (P) varies largely with sources, and availability of these nutrients once applied to soil still remains unknown. Five PBs differing in their C/N ratio (12-47) were used in an incubation study to assess the P forms and availability from both PBs and PB-amended soils. Biosolids were added to three contrasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Similarly, we found that the soil P fraction pool across these different plant community structures and soil horizon depths was dominated by the stable Ca-bound P fraction (HCl-P), which comprised 85.5% of the total soil P budget in the A horizon and 84.9% in the B horizon of the soil. The resin-extractable P represents the most labile pool of Pi and Po, followed by the bicarbonate-extractable Pi and Po [83,84]. The A. sparsifolia monoculture could absorb labile P and increase the proportions of resin-extractable P and bicarbonate-extractable Pi in the soil B horizon better than the K. caspia monoculture or intercropped plots (Figure 3).…”
Section: Phosphorus Cycling Across the Monoculture And Intercropping ...mentioning
confidence: 98%
“…Similarly, we found that the soil P fraction pool across these different plant community structures and soil horizon depths was dominated by the stable Ca-bound P fraction (HCl-P), which comprised 85.5% of the total soil P budget in the A horizon and 84.9% in the B horizon of the soil. The resin-extractable P represents the most labile pool of Pi and Po, followed by the bicarbonate-extractable Pi and Po [83,84]. The A. sparsifolia monoculture could absorb labile P and increase the proportions of resin-extractable P and bicarbonate-extractable Pi in the soil B horizon better than the K. caspia monoculture or intercropped plots (Figure 3).…”
Section: Phosphorus Cycling Across the Monoculture And Intercropping ...mentioning
confidence: 98%
“…The use of papermill biosolids could be an attractive soil amendment alternative in agriculture and forestry. They are rich in Ca, also contain N, P and K (but in lesser amount than municipal biosolids), and due to a high fiber content they can augment soil structure, organic carbon and cation exchange capacity (Chantigny et al 1999;Camberato et al 2006, Zhang et al 2020. Papermill biosolids potentially minimize environmental risks compared to municipal biosolids because they contain less heavy metals than municipal biosolids and do not lead to critical levels in plants after they are applied on agricultural fields (Gagnon et al 2013).…”
Section: Introductionmentioning
confidence: 99%